(untitled) (Journal of the College of Education for Women, 2018)
The present research deals with the spatial variance analysis in Jwartadistrict and conducting a comparison on the spatial and seasonal changes of the vegetation cover between (2007-2013) in order to deduce the relationship between the vegetation density and the areas which are exposed to the risk of water erosion by using Plant Variation Index NDVI) C (coefficient and by using Satellite images of Landsat satellite which are taken in 2/7/2007 and Satellite images of Landsat satellite taken in 11/1/ 2013, the programs of remote sensitivity and the Geographic Information Systems. The study reveals that there is a variance in the density of vegetation cover of the area under study betwee 2007 and 2013. However, the Satellite images of Landsat satellite show that there is a scarcity of vegetation in 2007 in comparison with 2013 where there is a thick vegetation cover. The correlation relationship by using the Pearson coefficient reveals that there is a proportional correlation between density of vegetation and rainfall and shows also that there is a reversal correlation between the land area and the amount of rain falling. However, this indicates that the years of little rain reflects the distribution of low density plant and this exposes these areas into risk of erosion whereas the years of heavy rainfall indicat to heavy plant distribution and this will have influence in reducing the amount of lands that may ionexpose to eros.